Desempenho e digestibilidade de componentes nutritivos de dietas contendo subprodutos de leaginosas na alimentação de cordeiros - Santos, Viviane Correa [UNESP]; Bertocco Ezequiel, Jane Maria [UNESP]; Morgado, Eliane da Silva [UNESP]; Favaro, Vanessa Ruiz [UNESP]; D'Aurea, Andre Pastori [UNESP]; Sousa Junior, Severino Cavalcante de (Univ Estadual Londrina, 2014)
The aim of this work was evaluate introduction of byproducts of oleaginous in lambs feeding. Diets were composed for 30% of Tifton hay and 70% of concentrate based on corn grain, soybean meal, soybean cake, sunflower cake and peanut cake, limestone and mineral mixture, as dites: FS - control with soybean meal, TS - soybean cake as part of the concentrate, TG sunflower cake as part of the concentrate and TA - peanut cake as part of the concentrate. For performance evaluating 24 Santa Ines lambs with initial age and weight of 70 days and 19 +/- 2 kg, according to a completely randomized design. For digestive evaluate, weight Santa Ines sheep with initial age and weight of 70 days and 16 +/- 1.2 kg, adapted to the use of bag, for collect feces. Animals were distributed in a replicated 4 x 4 Latin Square and means were compared by Tukey's test with 5% significance level. By the performance trial, duration of confinement, weight gain, fed conversion and the dry matter intake were not affected (P>0,05), with averages of 54.29 days, 259 g/day, 4.29 kg of DM/kg and 1.32 kg/day, respectively. There were no difference P>0,05) for intake DM, OM, CP, CT and CE among diets, digestibility trial with averages of 76.23; 74.47; 76.44; 41.12; 73.00 and 93.00%, respectively. There were no differences for digestibility DM, OM, CP, ADF, CT and NCF. The partial substitution of the soybean meal for byproducts of oleaginous was a good proteic alternative in the feeding of lambs.
Performance and digestibility of nutritional components of diets containing byproducts of oleaginous in lambs feeding
Keywords: Peanut cake; protein; soybean cake; sunflower cake; sheep